Efecto de la densidad de siembra en el rendimiento de híbridos experimentales de Maíz (Zea maíz) Amarillo duro en invierno en la costa peruana - Rosales Bardales, Alexander (2004)
This thesis aimed to determine the hybrid combination - planting density - number of plants per hole to achieve the highest grain yield in winter planting in the Peruvian coast. It was carried out between June 2003 and January 2004, in the district of La Molina, Lima Province - Lima, located 76® 57 '00 "longitude, 12® 05' 06" latitude and altitude of 243.7 m We worked six experimental hybrids triple and a witness hybrid Agraceras the effect of planting density and number of plant performance hit hard winter yellow corn on the Peruvian coast was assessed; as well as other complementary vegetative crop characteristics. the statistical design of randomized complete block factorial arrangement 7x2x2 with 28 treatments and 3 replicates per treatment and the results were analyzed using analysis of variance, Duncan test and coefficient of variability was used. The experimental soil was loam slightly alkaline reaction (pH 7.6) containing low organic matter (1.5%), carbonate high calcium (2.2), the content normal phosphorus (8.5 ppm) and potassium interchangeable low (0.27 meq / 100gr.). Sowing was done on dry land in a traditional way, using a gap of 0.80 m between rows and 0.40 m, 0.50 m, 0.60 m and 0.75 m between plants, leaving 2 and 3 plants for blow, making a density per hectare of 50 000 62,500 plants / ha. The crop received 5 furrow irrigation and fertilization was done using the dose 180-80 -80 units NPK respectively. Composting was applied in installments, half the dose of nitrogen, all the phosphorus and potassium at 15 days after planting and the balance nitrogen was applied to 62 days after planting. According to the results of the statistical analysis it found that the hybrid AGROCERES (H7) had the highest yield with 10.57 t / ha. NEXT ^ ole-eUiíbddQiH ^ ^ CEM I) x (123x118) with a yield de972 t / ha. the yield was lower hybrid H4 (PM-701) x (367x365) with a yield of 8.65 t / ha. Densities for the highest performance was achieved using the highest density of planting 62,500 plants / ha. when it is 2 floors / blow evaluated for grain yield character. The arrangement of having two plants / blow was more favorable only when it is combined with 62 plants / ha. evaluated for grain yield character